Digest: Species collapse from disturbance occurs quickly, and recovery is slow*. (12th July 2019) - VanWallendael, Acer
Abstract: In certain conditions, newly‐formed species pairs may revert to one species. Zhang et al. modeled the impact of disturbance on incipient species in a predator‐prey model and found that species collapse may occur rapidly following disturbance. A distinct species pair can sometimes be re‐established if previous conditions are restored, but this depends on the type of disturbance as well as the amount of time that passes after a collapse.